Maturação somática e o relacionamento entre variáveis minerais ósseas e modalidades esportivas em adolescentes: Estudo transversal - Agostinete, Ricardo Ribeiro [UNESP]; Ito, Igor Hideki [UNESP]; Kemper, Han; Pastre, Carlos Marcelo [UNESP]; Rodrigues-Júnior, Mário Antônio [UNESP]; Luiz-De-Marco, Rafael [UNESP]; Fernandes, Rômulo Araújo [UNESP] (FapUNIFESP (SciELO), 2017)
CONTEXT AND OBJECTIVE: Peak height velocity (PHV) is an important maturational event during adolescence that affects skeleton size. The objective here was to compare bone variables in adolescents who practiced different types of sports, and to identify whether differences in bone variables attributed to sports practice were dependent on somatic maturation status. DESIGN AND SETTING: Cross-sectional study, São Paulo State University (UNESP). METHODS: The study was composed of 93 adolescents (12 to 16.5 years old), divided into three groups: no-sport group (n = 42), soccer/basketball group (n = 26) and swimming group (n = 25). Bone mineral density and content were measured using dual-energy x-ray absorptiometry and somatic maturation was estimated through using peak height velocity. Data on training load were provided by the coaches. RESULTS: Adolescents whose PHV occurred at an older age presented higher bone mineral density in their upper limbs (P = 0.018). After adjustments for confounders, such as somatic maturation, the swimmers presented lower values for bone mineral density in their lower limbs, spine and whole body. Only the bone mineral density in the upper limbs was similar between the groups. There was a negative relationship between whole-body bone mineral content and the weekly training hours (β: -1563.967; 95% confidence interval, CI: -2916.484 to -211.450). CONCLUSION: The differences in bone variables attributed to sport practice occurred independently of maturation, while high training load in situations of hypogravity seemed to be related to lower bone mass in swimmers.
Somatic maturation and the relationship between bone mineral variables and types of sports among adolescents: Cross-sectional study
Keywords: Adolescent; Bone density; Growth and development; Puberty; Sports